Identifying patterns of alumni commitment in key strategic relationship programmes - Pedro, Ilda; Pereira, Luís Nobre (ICAReAlumni Conference Proceedings, 2020)
In the last decades, higher education institutions (HEIs) worldwide face drastic changes due to diverse reasons such as demographic factors, financial crisis, globalisation, and international rankings, which are forcing these institutions to rethink their management practices and to adopt new approaches towards their stakeholders with an attentive focus on students as the main customers. Later on, the enhancement of long and lasting relationships with alumni as true partners becomes a new challenge; they thus use marketing strategies that highlight relationship marketing to develop strong bonds with alumni based on commitment.